2023
DOI: 10.1097/cm9.0000000000002459
|View full text |Cite
|
Sign up to set email alerts
|

Integrins in human hepatocellular carcinoma tumorigenesis and therapy

Abstract: Integrins are a family of transmembrane receptors that connect the extracellular matrix and actin skeleton, which mediate cell adhesion, migration, signal transduction, and gene transcription. As a bi-directional signaling molecule, integrins can modulate many aspects of tumorigenesis, including tumor growth, invasion, angiogenesis, metastasis, and therapeutic resistance. Therefore, integrins have a great potential as antitumor therapeutic targets. In this review, we summarize the recent reports of integrins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“… 43 Furthermore, upregulation of α V β 5 induced HCC proliferation and drove HCC angiogenesis. 20 From our meta-analysis result, we demonstrated that the gene expression of ITGAV and ITGB5 , analysed from obtained samples in GEO, was significantly upregulated in HCC tissues compared with normal liver tissue. To underscore the safety of using the particle, we previously demonstrated that a panel of normal human primary cells from various histological origins do not express or have extremely low expression of the RGD4C binding partners, α V β 3 and α v β 5 integrin receptors.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“… 43 Furthermore, upregulation of α V β 5 induced HCC proliferation and drove HCC angiogenesis. 20 From our meta-analysis result, we demonstrated that the gene expression of ITGAV and ITGB5 , analysed from obtained samples in GEO, was significantly upregulated in HCC tissues compared with normal liver tissue. To underscore the safety of using the particle, we previously demonstrated that a panel of normal human primary cells from various histological origins do not express or have extremely low expression of the RGD4C binding partners, α V β 3 and α v β 5 integrin receptors.…”
Section: Discussionmentioning
confidence: 79%
“…To underscore the safety of using the particle, we previously demonstrated that a panel of normal human primary cells from various histological origins do not express or have extremely low expression of the RGD4C binding partners, α V β 3 and α v β 5 integrin receptors. 20 These findings suggest that TPA is an appropriate delivery method for therapeutic genes to HCC.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Integrin family members are known as key regulators in cancer cell stemness, epithelial-mesenchymal transformation and extracellular matrix to initiate the metastatic process for multiple cancer types including breast cancer 19,25 . Importantly, unbiased analysis of the public database TMIER2 26 revealed a strong and statistically signi cant positive correlation nearly in all types, 37 out of total 40 of human cancers (Fig.…”
Section: Usp22 Promotes Breast Csc Self-renewal Through Upregulating ...mentioning
confidence: 99%
“…In this study, we present evidence that USP22 is highly expressed in breast cancer stem cells and required for both breast cancer initiation and metastasis. Both genetic and pharmacological USP22 inhibition largely reduced the breast cancer stem cell pool through down-regulating integrin b1, also known as CD29, a cell surface glycoprotein that is critical in almost every step of cancer progression, including cancer initiation, proliferation, local invasion, and metastatic colonization of the new tissue 18,19 .…”
Section: Introductionmentioning
confidence: 99%